This ardent flame [large type] - Kanell, Beth (Kanell, Beth, Winds of freedom, 2021)
"Alice Sanborn, seventeen years old in October 1852, expects Abolitionist political operative Solomon McBride to court her. Surely he visits for more than her insight and family connections in the Vermont farming village of North Upton! When Almyra Alexander, niece of the local minister, arrives in North Upton, she brings Boston sophistication and advanced political ideas. Temperance! Voting rights for women! Alice wants it all and Almyra's friendship, too-but is this newcomer a rival for Solomon's affections? Friendship with Caroline Clark looks safer: Newly returned to the village, Caroline is deaf and fluent in American Sign Language, which Alice quickly learns. Her friends and her demand for Abolition propel Alice into action. Assist neighbors at risk? Rescue a horse? Capture an arsonist? She's on it. Betrayal and danger lie ahead. Yet the three young women race into the righteous battle. For Alice and her friends, there's no other choice"-"--